Effect of iron gel on dentin permeability - Sales-Peres,Sílvia Helena de Carvalho (2011)
This study evaluated in vitro the effect of an experimental gel containing iron on the reduction of hydraulic conductance of dentin. Thirty-six 1-mm-thick dentin discs obtained from extracted human third molars were divided into 3 groups of 10 specimens each. The groups corresponded to the following experimental materials: 1.23% acidulated phosphate fluoride gel, pH 4.1; 3% potassium oxalate gel, pH 4.1 (Oxa-Gel®); and iron sulfate gel (10 mmol/L FeSO4), pH 4.1. The gels were applied to dentin under the following conditions: after 37% phosphoric acid and before 6% citric acid. Data were analyzed statistically by ANOVA and Tukey's test at 5% significance level. There was no significant differences (p<0.05) among the groups in any of the conditions for hydraulic conductance reduction, except for smear layer presence. The active agents reduced dentin permeability, but they produced significantly lower (p<0.05) reduction in hydraulic conductance when compared to presence of smear layer. The effectiveness in reducing dentin permeability was not significantly different (p>0.05) among the gels. This study suggests that the iron gel promoted reduction in dentin permeability comparable to that of the other agents and thus may be considered a good clinical alternative for the treatment of dentin hypersensitivity.